Bacterial Infections Associated with Cutaneous Leishmaniasis - Lafi, Shehab A; AL-Mawala, Saleem O; AL-Ani, Ali Abdul-Latef; AL-Dulaym, Abdulla S (AL-Kindy College Medical Journal, 2007)
Background:Oriental sore occurs mostly in themediteranian region , North Africa ,and the Middle East .Rodents are the main reservoir for the parasite . The wettype caused by L. major is rural and the dry type caused byL. tropica is urban and humans are presumably the onlyreservoir. Sand fly vectors are involved in all forms.Objectives: This study aimed to show the mostimportant bacterial infections concomitant with cutaneousleishmaniasis .Methods; The study was performed on 75 patients (ages1-50 years ) from both sexes were attending Skin DiseasesDepartment of Ramadi General Hospital during the periodextended from January to June 2000. These patients wereclinically diagnosed as patients with cutaneousleishmaniasis. Skin specimens were taken forbacteriological and parasitological investigations .The samething was done for specimens from 25 intact individualsresembling the test group as negative controls.Results: Children showed more lesions with Positivecutaneous leishmaniasis, adult females, showed more llesions than adult males. Children showed more bacterialisolates than adults, from both positive and negative llesions. Staphylococcal and Streptococcal isolates took thefirst rank of isolation in all age groups and both sexes. E.coli and fecal Streptococci were isolated from childrenonly.Conclusion: Bacterial invasion for the skin lesion withcutaneous leishmaniasis complicates the lesion and leads tomisdiagnosis, in addition to the delay of healing of thelesion via bacterial end-products. There is a need foraccurate diagnostic techniques like polymerase chainreaction (PCR) for both bacterial and parasitic agents,suitable effective antimicrobial therapy, in addition to theantileishmanial agents. Good sanitation of the lesion andcommunity education to prevent infections